2016
DOI: 10.1016/j.msea.2016.02.039
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural modeling of transgranular and intergranular fracture in crystalline materials with coincident site lattice grain-boundaries: Σ3 and Σ17b bicrystals

Abstract: The competing microstructural failure mechanisms of transgranular (TG) and intergranular (IG) fracture, in martensitic steel bicrystals with coincident site lattice (CSL) boundaries of Σ3 and Σ17b, have been investigated, using a dislocation-density-based crystalline plasticity formulation and a recently developed overlapping fracture method. A dislocation-density grain boundary (GB) interaction scheme was coupled within a dislocation-density based crystal plasticity formulation to investigate how different ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…The dislocation line can easily cross a grain boundary, as shown in Figure b. The grain boundaries affect the density of movable dislocations, which, in turn, determined mechanical properties, such as the microstructural strength and ductility of X80 pipeline steel.…”
Section: Test Results and Discussionmentioning
confidence: 99%
“…The dislocation line can easily cross a grain boundary, as shown in Figure b. The grain boundaries affect the density of movable dislocations, which, in turn, determined mechanical properties, such as the microstructural strength and ductility of X80 pipeline steel.…”
Section: Test Results and Discussionmentioning
confidence: 99%
“…Wu and Zikry [ 26 ] studied that the stress relief in crack tip during deformation was strongly affected by Σ3 (twin) boundaries, and Σ17b boundaries (86.63° <110>) blocked the growth of cleavage cracks. Although the glide plane of Fe–Si alloy may be {110}, {112} or {123} planes, the glide direction is always <111>.…”
Section: Discussionmentioning
confidence: 99%
“…Zikry et al found that CSL boundaries impeding dislocation transmission were prone to dislocation pile‐up and accumulation, and the stress relief in crack tip could be strongly influenced by the bicrystal with Σ3 CSL boundaries, in addition, the accelerated growth of cracks significantly decreased due to the effect of Σ17b (86.63°<110>) CSL boundaries. In comparison with the other CSL boundaries, Σ3 CSL boundaries are most beneficial to the plasticity required to prevent failure in service.…”
Section: Discussionmentioning
confidence: 99%